PENAMPILAN REPRODUKSI SAPI BALI PADA SISTEM PEMELIHARAAN SEMI INTENSIF - Alfonthodus I. Pian; Tarsisius C. Tophianong; Cynthia D Gaina (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2020)
Bali cattle is one of the native cattle in Indonesia. High fertility and are capabled to adapt well in tropical environment is one of the superiority of bali cattle. Bali cattle farming in East Nusa Tenggara (NTT) are generally managed by intensive, semi-intensive and extensive system traditionaly, without any recording and lacking good breeding practices. The purpose of this research is to determine the reproduction performance of bali cattle on semi-intensive management system based on pregnancy rate, days open and calving interval. The number of cattles used in this study were 40 cows on age 4-7 years. The methods used were interviews and rectal palpation to know the reproductive status of livestock. Descriptive analysis was used in this research. The results showed that the pregnancy rate was 45%, days open was 112,5 days and calving interval was 13,075 months. This study indicated a decreased reproductive efficiency of bali cattle in Kupang Regency, hence an improvement of the management reproduction is required to achieve good reproductive management.